Safety evaluation and risk assessment on a selected pipe welding services workshop for oil and gas industry /Khairi Najmi Mahusain - Khairi Najmi , Mahusain (2017)
This study was conducted on a selected pipe welding workshop for the oil and gas industry. The objectives of the study are to identify hazards, assess and evaluate the inherent risks in the pipe welding and related activities. Control measures will be proposed to reduce risks associated with the hazards. In order to achieve that goal, several methods have been implemented to obtain the essential information and data. Workplace visits were conducted to feed more detailed information on the pipe welding process and monitor the hazards at work. Existing control measures were recorded for the risk assessment process. The results of the workplace assessment shall determine the risk rating. By applying this assessment method, hazards at the workplace shall be divided according to the level of risk rating whether HIGH, MEDIUM or LOW. Result of the risk rating study shows no risk of HIGH, while 37 hazards were MEDIUM and 8 hazards were LOW. Installation of Local Exhaust Ventilation (LEV) is highly recommended for all welding stations to reduce exposure to welding fumes. The installation of portable sound dampener is also recommended for pipe beveling machines to reduce loud noise at the workplace. Workers' commitment and support from company management are crucial for creating and pursuing a healthier and safer workplace.